2015
DOI: 10.18632/oncotarget.5991
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil resistant colon cancer cells are addicted to OXPHOS to survive and enhance stem-like traits

Abstract: Despite marked tumor shrinkage after 5-FU treatment, the frequency of colon cancer relapse indicates that a fraction of tumor cells survives treatment causing tumor recurrence. The majority of cancer cells divert metabolites into anabolic pathways through Warburg behavior giving an advantage in terms of tumor growth. Here, we report that treatment of colon cancer cell with 5-FU selects for cells with mesenchymal stem-like properties that undergo a metabolic reprogramming resulting in addiction to OXPHOS to mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 52 publications
6
93
1
Order By: Relevance
“…We have previously demonstrated that colon cancer‐resistant cells acutely treated with 5‐FU modulate their metabolism and undergo epithelial‐mesenchymal transition, increasing stemness and aggressiveness. Nevertheless, we demonstrated that it is possible to revert resistance of cancer cells by interfering with molecular mechanisms that mediate the adaptive response . Based on this evidence, we speculate that the adaptive response of resistant cells could be modulated by altered miRNA expression.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…We have previously demonstrated that colon cancer‐resistant cells acutely treated with 5‐FU modulate their metabolism and undergo epithelial‐mesenchymal transition, increasing stemness and aggressiveness. Nevertheless, we demonstrated that it is possible to revert resistance of cancer cells by interfering with molecular mechanisms that mediate the adaptive response . Based on this evidence, we speculate that the adaptive response of resistant cells could be modulated by altered miRNA expression.…”
Section: Introductionmentioning
confidence: 70%
“…To investigate the contribution of miRNAs expression in the acquisition of chemoresistance, we used as a model a HT29 human colon cancer cell line resistant to 5‐FU (HT29R). HT29R cells were obtained exposing HT29 cells to increasing doses of 5‐FU, as previously described . A profiled miRNA expression analysis on microarray platform pointed out 98 of the 382 considered miRNAs differently expressed between HT29 and HT29R cells (Table S1), thereby confirming that resistant cells undergo strong genetic reprogramming.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…HT29 and HCT‐116 resistant to 5‐FU (HT29R and HCT‐116R, respectively) were selected by exposing HT29 or HCT‐116 sensitive cells to increasing doses of 5‐FU during 6 months until the final concentration of 20 μM, as previously described …”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of colorectal cancer has been incresed along the increasing human population (ACS, 2014). First line therapy for CRC, 5-fluorouracil (5FU) has been become resistence despite its side effect like neutropenia, immunosuppression, cardiotoxicity and diarrhea (Denise, et al, 2015;Gressett, et al, 2006;Sorrentino, et al, 2012). *Corresponding author e-mail : ririsjenie@gmail.com Recently, natural products have received great interest since they have relatively few side effects compared with modern chemotherapeutics and have been used clinically for thousands of years as significant alternative remedies for a variety of diseases including cancer (Kellof, 2000;Jeune, et al, 2005;Won, et al, 2006).…”
Section: Introductionmentioning
confidence: 99%